The Savant and the State : Science and Cultural Politics in Nineteenth-Century France - Fox, Robert, 1938- (Book collections on Project MUSE., 2012)
"There has been a tendency to view science in nineteenth-century France as the exclusive territory of the nation's leading academic centers and the powerful Paris-based administrators who controlled them. Ministries and the great savants and institutions of the capital seem to have defined the field, while historians have ignored or glossed over traditions on the periphery of science. In The Savant and the State, Robert Fox charts new historiographical territory by synthesizing the practices and thought of state-sanctioned scientists and those of independent communities of savants and commentators with very different political, religious, and cultural priorities. Fox provides a comprehensive history of the public face of French science from the Bourbon Restoration to the outbreak of the Great War. Following the Enlightenment, many different interests competed to define the role of science and technology in French society. Political and religious conservatives tended to blame the scientific community for upsetting traditional values and, implicitly, delivering France into the hands of revolutionary extremists and Napoleonic bureaucrats. Scientists, for their part, embraced the belief that observation and experimentation offered the surest way to the knowledge and wisdom on which the welfare of society depended. This debate, Fox argues, became a contest for the hearts and minds of the French citizenry."--Project Muse.